Penerapan Model Pembelajaran Probing Prompting Terhadap Hasil Belajar Ekonomi Siswa Kelas XI IPS SMA Negeri 1 Habinsaran - Pardosi, Vianni R; Sinaga, Dearlina; Siagian, Lasma (Jurnal Kajian Ilmu Pendidikan (JKIP), 2025)
This study was motivated by the low learning outcomes of students in Economics subjects at senior high school, which are partly caused by the use of conventional teacher-centered learning methods. Therefore, this research aims to determine the effectiveness of the Probing Prompting learning model in improving student learning outcomes. The research employed an experimental method with a Pretest-Posttest Control Group Design. The sample consisted of two classes: the experimental class (35 students) taught using the Probing Prompting model, and the control class (36 students) taught using conventional methods. Learning outcome data were collected through pretest and posttest, and analyzed using descriptive statistics, normality test, homogeneity test, t-test, and N-Gain calculation. The results revealed that there was a significant difference in learning outcomes between the experimental and control classes. The average posttest score of the experimental class was 27.06, higher than that of the control class at 18.69. The t-test results showed tcount = -9.247 > ttable = 0.67806 with a p-value = 0.000 < 0.05. In addition, the N-Gain of the experimental class reached an average of 0.8110 or 81.10%, categorized as high, while the control class was only in the low category. Based on these findings, it can be concluded that the Probing Prompting learning model is effective in teaching Economics at the senior high school level. This model not only significantly improves learning outcomes but also encourages students to be more active, engage in interaction, and develop critical thinking skills during the learning process.